2008
DOI: 10.1002/da.20291
|View full text |Cite
|
Sign up to set email alerts
|

Learning and memory impairment in PTSD: relationship to depression

Abstract: Memory function was studied in combat veterans with posttraumatic stress disorder (PTSD), combat veterans without PTSD, and noncombat veterans. The Vocabulary and Digit Span subtests of the WAIS and Logical Memory (LMS) and Verbal Paired Associates (VPAS) subtests of the Wechsler Memory Scale III were administered. Combat veterans with PTSD showed impaired memory on the LMS and VPAS compared to combat veterans without PTSD or noncombat veterans. Veterans with PTSD also showed lower WAIS Vocabulary subtest scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 34 publications
1
45
1
Order By: Relevance
“…Therefore, the neurocognitive profile found in this meta-analysis does not appear to reflect general distress or psychopathology. Moreover, although some authors have posited that the cognitive deficits observed in PTSD are primarily due to depressive symptomatology in the context of PTSD (e.g., Burriss et al, 2008; Johnsen et al, 2008; Olff et al, 2014), this pattern of deficits (in combination with negative results in our analyses of the effect of depression on effect size variance) argues against this hypothesis.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, the neurocognitive profile found in this meta-analysis does not appear to reflect general distress or psychopathology. Moreover, although some authors have posited that the cognitive deficits observed in PTSD are primarily due to depressive symptomatology in the context of PTSD (e.g., Burriss et al, 2008; Johnsen et al, 2008; Olff et al, 2014), this pattern of deficits (in combination with negative results in our analyses of the effect of depression on effect size variance) argues against this hypothesis.…”
Section: Discussionmentioning
confidence: 58%
“…2 Some recent studies examined cognitive deficits in PTSD without assessing effort but yielded interesting findings. Burriss et al (2007) reported that depressive symptoms mediated the cognitive deficits they observed in PTSD patients (see also Johnsen et al 2008), although Rohling et al (2002) and Green (2008) reported that depression does not produce lowered cognitive scores when examinees exert good effort. Johnsen et al (2008) reported deficits on delayed recall, which was mediated by less efficient learning in the PTSD sample.…”
Section: Assessment Of Ptsd In Forensic and Compensation Contextsmentioning
confidence: 95%
“…Individuals diagnosed with PTSD often display significant impairment in social, occupational, cognitive, and health functioning (Burriss, Ayers, Ginsberg, & Powell, 2008;Davidson, 2001) along with elevated suicide rates (Benda, 2005). Fortunately, a great deal of research suggests evidence-based treatments (EBTs), such as prolonged exposure (PE; Foa, Hembree, & Rothbaum, 2007) and cognitive processing therapy (CPT; Resick, Monson, & Chard, 2010) are effective in reducing PTSD symptoms in outpatient (Rizvi, Vogt, & Resick, 2009;Tuerk et al, 2012) and residential settings (Chard, Schumm, McIlvain, Bailey, & Parkinson, 2011).…”
mentioning
confidence: 99%